VD_FINDINFO Décision / 2015 / 134 vom 4. Februar 2015 - VD Tribunal cantonal (2015)
CLASSEMENT DE LA PROCÉDURE, MOYEN DE DROIT, JUGE UNIQUE, PRESCRIPTION | 109 CP, 97 al. 3 CP, 329 al. 4 CPP (CH), 395 let. a CPP (CH)